Innate immunity changes in soccer players after whole-body cryotherapy - Valentina Selleri; Marco Mattioli; Domenico Lo Tartaro; Annamaria Paolini; Giada Zanini; Anna De Gaetano; Roberta D'Alisera; Laura Roli; Alessandra Melegari; Pasqualino Maietta; Ferdinando Tripi; Emanuele Guerra; et al. (BMC, 2022)
Abstract Whole-body cryotherapy (WBC) consists of short exposure (up to 2-3 min) to dry air at cryogenic temperatures (up to -190 °C) and has recently been applied for muscle recovery after injury to reduce the inflammation process. We aimed to determine the impact of cryotherapy on immunological, hormonal, and metabolic responses in non-professional soccer players (NPSPs). Nine male NPSPs (age: 20 ± 2 years) who trained regularly over 5 consecutive days, immediately before and after each training session, were subjected to WBC treatment (WBC-t). Blood samples were collected for the evaluation of fifty analytes including hematologic parameters, serum chemistry, and hormone profiles. Monocytes phenotyping (Mo) was performed and plasmatic markers, usually increased during inflammation [CCL2, IL-18, free mitochondrial (mt)DNA] or with anti-inflammatory effects (IL2RA, IL1RN), were quantified. After WBC-t, we observed reduced levels of ferritin, mean corpuscular hemoglobin, mean platelet volume, testosterone, and estradiol, which however remain within the normal ranges. The percentage of the total, intermediates and non-classical Mo increased, while classical Mo decreased. CXCR4 expression decreased in each Mo subset. Plasma IL18 and IL2RA levels decreased, while IL1RN only exhibited a tendency to decrease and CCL2 showed a tendency to increase. Circulating mtDNA levels were not altered following WBC-t. The differences observed in monocyte subsets after WBC-t may be attributable to their redistribution into the surrounding tissue. Moreover, the decrease of CXCR4 in Mo subpopulations could be coherent with their differentiation process. Thus, WBC through yet unknown mechanisms could promote their differentiation having a role in tissue repair.